The privacy and security implications of open data in healthcare - Kobayashi, S; Kane, T; Paton, C (Schattauer, 2018)
The International Medical Informatics Association (IMIA) Open Source Working Group (OSWG) initiated a group discussion to discuss current privacy and security issues in the open data movement in the healthcare domain from the perspective of the OSWG membership. Working group members independently reviewed the recent academic and grey literature and sampled a number of current large-scale open data projects to inform the working group discussion. This paper presents an overview of open data repositories and a series of short case reports to highlight relevant issues present in the recent literature concerning the adoption of open approaches to sharing healthcare datasets. Important themes that emerged included data standardisation, the inter-connected nature of the open source and open data movements, and how publishing open data can impact on the ethics, security, and privacy of informatics projects. The open data and open source movements in healthcare share many common philosophies and approaches including developing international collaborations across multiple organisations and domains of expertise. Both movements aim to reduce the costs of advancing scientific research and improving healthcare provision for people around the world by adopting open intellectual property licence agreements and codes of practice. Implications of the increased adoption of open data in healthcare include the need to balance the security and privacy challenges of opening data sources with the potential benefits of open data for improving research and healthcare delivery.